2007
DOI: 10.1016/j.media.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of vessel-based registration for correction of brain shift

Abstract: The displacement and deformation of brain tissue is a major source of error in image-guided neurosurgery systems. We have designed and implemented a method to detect and correct brain shift using pre-operative MR images and intraoperative Doppler ultrasound data and present its validation with both real and simulated data. The algorithm uses segmented vessels from both modalities, and estimates the deformation using a modified version of the iterative closest point (ICP) algorithm. We use the least trimmed squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 54 publications
(49 reference statements)
1
73
0
Order By: Relevance
“…This is achieved by maximizing the mutual information ͑MI͒ between the iUS and pMR. Other feature-based methods of registering these two image modalities require segmentation of anatomical structures ͑e.g., surfaces 11 or vessels 12 ͒, which can be difficult to automate and usually requires manual ͑time consuming͒ intervention especially in the US images. Application of MI-based registration of US images is relatively unexplored, 13 and only a limited number of studies have been reported ͑e.g., between US and MR for brain, 14,15 liver, 16 and phantom images; 17 between US and MR angiography of carotid arteries; 18 between US and CT for kidney; 19 between cardiac US and SPECT; 20 and between US and US for abdominal and thoracic organs 21 and breast 22 ͒.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by maximizing the mutual information ͑MI͒ between the iUS and pMR. Other feature-based methods of registering these two image modalities require segmentation of anatomical structures ͑e.g., surfaces 11 or vessels 12 ͒, which can be difficult to automate and usually requires manual ͑time consuming͒ intervention especially in the US images. Application of MI-based registration of US images is relatively unexplored, 13 and only a limited number of studies have been reported ͑e.g., between US and MR for brain, 14,15 liver, 16 and phantom images; 17 between US and MR angiography of carotid arteries; 18 between US and CT for kidney; 19 between cardiac US and SPECT; 20 and between US and US for abdominal and thoracic organs 21 and breast 22 ͒.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the influence of possible outliers on the registration result, the algorithm was modified by incorporating the Least Trimmed Squares (LTS) robust estimator as described by Reinertsen et al [10].…”
Section: Registrationmentioning
confidence: 99%
“…This is a big challenge as the 3D registration of TTE to MRI remains to be an open problem. To date, most existing approaches for echo to MRI (or CT) registration have been used in neurosurgical applications [2,3]. Cardiac echo-MR registration has been addressed to a lesser extent [4][5][6].…”
Section: Introductionmentioning
confidence: 99%